Coordination and Cooperation in E‐Government: An Indonesian Local E‐Government Case. Issue 1 (5th December 2017) - Nurdin, Nurdin; Stockdale, Rosemary; Scheepers, Helana
Abstract: The implementation of e‐government systems often involves many different agencies and actors. Their different characteristics and the need to work together make the relationships between them complex. Coordination and cooperation have become important issues in harmonizing the many actors that support the implementation of e‐government systems. This study examines how coordination and cooperation shape the implementation process of local e‐government systems that may be acquired or developed internally. A case study of local egovernment systems implementation in Indonesia is presented and analyzed from the perspectives of coordination and cooperation between internal and external actors and agencies. Our findings suggest that dynamic coordination and cooperation have influenced the success of e‐government systems implementation at local government (regency) level in Bali, Indonesia. The regency practiced coordination and cooperation, both vertically and horizontally, with central government agencies, other regencies, private companies, and with internal institutions. The ability of the regency to gain from these practices offers insights into e‐government implementation for other local governments.